Improving the Academic Performance of Lower Academic Achievers’ of Alelitu Sagure Primary School Learners’ Using Tutorial and Guidance and Counseling Service - Woldetsadik, Dereje Adefris; Alemu, Birhanu Moges (European Journal of Applied Sciences, 2020)
The main aim of this action research project was to improve the academic achievement of lower academic achievers students of Alelitu Sagure primary school. Hence, students whose academic achievements were found to be lower than others selected on the base of the first semester academic records (on the bases of academic rank). In this regard 25 students from each grade level (Grade 2, 3, 5 and 6) were selected. In general, 2 grade levels from the first cycle (grade 1-4) and 2 grade levels from the second cycle (grade 5-8) were selected as the research participants. Among the school 12 teachers were selected and given orientation and trainings on how to implement the action research project. Besides, the student participants and their parent/guardians were oriented too. The tutorial classes were provided for the project students three hours per week, one hour for each of the three selected subjects (English, mathematics and science) as well guidance and counseling service were provided according to the condition. Generally, the findings of this action research project proven that the improvements of the academic performance of lower academic achiever students in general, and better improvement in the upper grade levels in particular. Furthermore, with the focus group and interviews made with the action research teacher participant their view and believes about lower academic achiever students were changed by which if lower academic achiever students assisted and given appropriate support as they could improve their academic performance.